Vulnerability and Just Desert: A Theory of Sentencing and Mental Illness - Johnston, E. Lea (2013)
This Article analyzes risks of serious harms posed to prisoners with major mental disorders and investigates their import for sentencing under a just deserts analysis. Drawing upon social science research, the Article first establishes that offenders with serious mental illnesses are more likely than non-ill offenders to suffer physical and sexual assaults, endure housing in solitary confinement, and experience psychological deterioration during their carceral terms. The Article then explores the significance of this differential impact for sentencing within a retributive framework. It first suggests a particular expressive understanding of punishment, capacious enough to encompass foreseeable, substantial risks of serious harm proximately caused by the state during confinement and addresses in particular the troublesome issue of prison violence. It then turns to just desert theory and principles of ordinal and cardinal proportionality to identify three ways in which vulnerability to serious harm may factor into sentencing. In so doing, the Article advances the current debate about the relevance of individual suffering to retributivism and lays the theoretical groundwork for the consideration of vulnerability due to mental illness as a morally relevant element in sentencing decisions